2007
DOI: 10.1524/zkri.2007.222.11.567
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of defect structures in nanocrystalline materials by X-ray line profile analysis

Abstract: Abstract. X-ray line profile analysis is a powerful alternative tool for determining dislocation densities, dislocation type, crystallite and subgrain size and size-distributions, and planar defects, especially the frequency of twin boundaries and stacking faults. The method is especially useful in the case of submicron grain size or nanocrystalline materials, where X-ray line broadening is a well pronounced effect, and the observation of defects with very large density is often not easy by transmission electr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(17 citation statements)
references
References 94 publications
(92 reference statements)
1
16
0
Order By: Relevance
“…The development of microstructural features at different length scales was examined through X-ray diffraction, EBSD and indentation techniques. First, the investigated materials were exposed to X-ray diffraction line profile analysis, which allows the dislocation density to be calculated by analyzing the broadening of diffraction lines by the method described in great detail in [6,8]. Both annealed and deformed samples were studied on the plane perpendicular to the normal direction (ND plane).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The development of microstructural features at different length scales was examined through X-ray diffraction, EBSD and indentation techniques. First, the investigated materials were exposed to X-ray diffraction line profile analysis, which allows the dislocation density to be calculated by analyzing the broadening of diffraction lines by the method described in great detail in [6,8]. Both annealed and deformed samples were studied on the plane perpendicular to the normal direction (ND plane).…”
Section: Methodsmentioning
confidence: 99%
“…Typically, the number of one-dimensional defects is determined using transmission electron microscopy (TEM), which provides a direct image of the substructure that has evolved. As an alternative to TEM, the quantity of dislocations can also be evaluated indirectly by X-ray diffraction line profile analysis (XLPA) [6][7][8], indentation techniques [9] or electron backscattering diffraction (EBSD) [10]. In XLPA, the data are obtained in the form of diffraction lines and the parameters of the defect structure are extracted by analyzing the width and shape of the diffraction peak profiles [6][7][8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that the break of coherency can occur even for dipolar dislocation walls, although they do not cause any misorientations between the domains [47]. Since the lattice defects fragment the grains into smaller coherently scattering domains, the crystallite size determined by XRD line profile analysis is usually smaller than the grain size obtained by TEM [48]. This difference depends on the processing method of the studied material.…”
Section: Introductionmentioning
confidence: 99%
“…The sample preparation is simple and the obtained characteristics are average of the entire sample. These can be empirical advantages over the powerful technique of transmission electron microscopy (TEM) (Tian and Atzmon, 1999; Gubicza and Ungar, 2007). Therefore, several XRD analysis methods have been developed to calculate the crystallite size, microstrain, or dislocation density in different lattice structures.…”
Section: Introductionmentioning
confidence: 99%